2014
DOI: 10.1016/j.jsps.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Public attitude and justification to purchase antibiotics in the Eastern region Al Ahsa of Saudi Arabia

Abstract: Use of non-prescription antibiotics can portend danger and predispose the populace to changes in bacterial resistance pattern. The aims of this study were to (a) evaluate the knowledge and attitudes of residents of Al-Ahsa community, Saudi Arabia on the use of non-prescribed antibiotics. (b) To identify possible predictors (if any) for self-medication within the community. A cross-sectional survey study, using self-administered questionnaire was conducted in two sections; demographics and self-medication attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 22 publications
(36 reference statements)
6
50
1
Order By: Relevance
“…This finding is similar to that unveiled by other studies, as that of Awad et al in Kuwait and Emeka et al in Al Ahsa, Saudi Arabia where the prevalence of self-medication among respondents was 27.5% and 73.7% respectively. 21,22 Similarly, about 16% of the participants in the current study requested antibiotic prescriptions via the phone; again indicating their confidence in self-medication. Thus, individuallevel characteristics predispose to this self-medication behaviour, such as: a perceived availability of antibiotics without prescription in certain countries, the high cost of a medical consultation, and the prevailing dissatisfaction towards medical practitioners.…”
Section: Discussionmentioning
confidence: 63%
“…This finding is similar to that unveiled by other studies, as that of Awad et al in Kuwait and Emeka et al in Al Ahsa, Saudi Arabia where the prevalence of self-medication among respondents was 27.5% and 73.7% respectively. 21,22 Similarly, about 16% of the participants in the current study requested antibiotic prescriptions via the phone; again indicating their confidence in self-medication. Thus, individuallevel characteristics predispose to this self-medication behaviour, such as: a perceived availability of antibiotics without prescription in certain countries, the high cost of a medical consultation, and the prevailing dissatisfaction towards medical practitioners.…”
Section: Discussionmentioning
confidence: 63%
“…Similar to other survey studies on antibiotic awareness, [9,10,16,17,19] this present study was also carried out in adults who were able to express their perceptions and understanding about antibiotic use and resistance. It should be noted that different studies have different objectives and emphases based on antibiotic circumstances.…”
Section: Discussionmentioning
confidence: 90%
“…This was quite similar to the study of McNulty et al [8] that noted one-third of the public still believe antibiotics are effective against coughs and colds. Emeka et al [10] also pointed out colds and sore throat are two important infections for which people tend to seek nonprescribed antibiotics for prevention rather than treatment. Although many patients themselves knew when they needed antibiotics, many of them did not want to get the medicines straightaway from pharmacies, except those being interviewed in the shops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the infections caused by the antibiotic resistant bacteria kill about twenty thousand patients annually in the USA and also leads to economic loss [3]. The cases of AMR bacterial infections are also increasing in the Kingdom of Saudi Arabia due to irrational use of antibiotics as well as due to the socio-economic and demographic characteristics of Saudi, non-Saudi and pilgrim population [4][5][6][7]. Another factor contributing to the development of AMR is failure to discover new antimicrobial agents [8][9][10].…”
Section: Introductionmentioning
confidence: 99%